Diabetes Mellitus and Its Complications in an Elderly Population - Abbott, M. M. (1964)
The planning of a diabetic control program in a home and hospital for the aged prompted a survey of the incidence, severity and number of complications of diabetes mellitus in this population. Twenty-eight per cent of the total population of 265 persons were found to be diabetic. In most of them the onset of diabetes was late in life and in the majority the disease was controlled by dietary measures alone. Of interest was the low incidence of gallbladder disease, hypercholesterolemia, ocular disease, myocardial and peripheral vascular disease. Neurological complications were minimal. The measures adopted to achieve biochemical stabilization in diabetes mellitus are discussed and the absence of acidosis and ketosis in this group is noted. The high incidence of diabetes, the need for detection of undiagnosed cases, and the low rate of complications are discussed.